The Selectivity of CK2 Inhibitor Quinalizarin: A Reevaluation. (19th October 2015) - Cozza, Giorgio; Venerando, Andrea; Sarno, Stefania; Pinna, Lorenzo A.
Abstract : Many polyphenolic compounds have been reported to inhibit protein kinases, with special reference to CK2, a pleiotropic serine/threonine kinase, implicated in neoplasia, neurodegenerative disease, and viral infections. In general however these compounds are not endowed with stringent selectivity. Among them quinalizarin (1, 2, 5, 8-tetrahydroxyanthraquinone) turned out to be particularly potent (Ki = 0.058 μ M) and quite selective as judged by profiling it on a small panel of 70 protein kinases. Here, by profiling quinalizarin on a larger panel of 140 kinases we reach the conclusion that quinalizarin is one of the most selective inhibitors of CK2, superior to the first-in-class CK2 inhibitor, CX-4945, now in clinical trials for the treatment of cancer. Moreover here we show that quinalizarin is able to discriminate between the isolated CK2 catalytic subunit (CK2 α ) and CK2 holoenzyme (CK2 α 2 β 2 ), consistent with in silico and in vitro analyses.